Leucose enzoótica bovina: uso de peptídeo sintético derivado da glicoproteína do envelope viral no imunodiagnóstico - Telissa da Cunha Kassar (2018)
Enzootic bovine leukosis (EBL) is an infectious lymphoproliferative disease of cattle caused by bovine leukemia virus (BLV), a member of the Retroviridae family, genus Deltaretrovirus. The EBL is characterized by persistent lymphocytosis and the presence of lymphosarcoma. It has anexpressive economic impact due to export losses, treatment of secondary infection; decrease of dairy production and also due to a differential handling required. Nevertheless, proviral DNA and structural virus proteins have been found in human tissues, especially those associated with breast cancer, suggesting that BLV could be transmitted naturally to humans. The main form for EBL diagnosis is by laboratory methods, once infected animals show no clinical signs or they are usually inconclusive. The diagnosis of EBL can be performed by molecular techniques and by the detection of specific antibodies in serum or milk samples. The infected animal develops a humoral immune response to viral proteins, primarily to gp51 (an envelope protein), and its identification is crucial for epidemiological surveillance, certification of disease-free areas, and prevalence studies. This work consists of a literature review chapter and of another chapter describing the development and standardization of an indirect ELISA using a synthetic peptide predicted in silico as antigen. The review chapter aims to describe the biology, epidemiology, pathogenesis, clinical signs and diagnoses for BLV, as well as the importance of this infection in the immune response of the animals, and present the latest evidencies on the possible human infection by BLV. The second chapter comprises the in silico prediction, the chemical synthesis of the linear peptide KIPDPPQPDFPQL, described as pgp51, and the subsequent standardization of the ELISA. The pgp51 ELISA was efficient to segregate positive and negative serum samples, indicating that it has a great potential to be used in the serological diagnosis of EBL. Afterward, the newly standardized ELISA-i was compared to commercialized available diagnostic tests. The indirect ELISA using synthetic peptide pgp51 after prediction of in silico epitopes obtained results comparable to the currently used diagnostic tests and thus it also can be used as diagnostic test for EBL in studies of prevalence in Brazil. In addition, the commercial tests showed divergence in the results for the diagnosis of BLV, which explicit need to reconsideration in the diagnostic system used currently.